A Procedural Algorithmic Approach for Functional Structure Construction - Mohammed Ο. Μ.; Shammari Α. Ζ. Μ. (Engineering, Technology & Applied Science Research, 2021)
Despite the advances in functional structure modeling, the underlying models are lacking formalism and a consistent basis for successive reasoning. Many researchers have worked on functional structures and in standardizing their vocabulary while some undertook the task of benchmarking the process of creating it, although the effects of functional structure modeling methods and strategies on further stages of conceptual design during concept generation have not been discussed in depth. In the present research, a new procedural algorithmic approach for the functional structure is developed and demonstrated.